Exploring the potential of Metarhizium species for the control of Euschistus heros (Hemiptera: Pentatomidae) - Aline Nunes-Silva; Camila Costa Moreira; Janaína Brandão Seibert; Jonathan Rodríguez; Italo Delalibera-Júnior (Biological Control)
Entomopathogenic fungi have been widely used for sustainable agriculture as biological pest control agents. However, commercially available isolates were not efficient in controlling the stink bug Euschistus heros (Hemiptera: Pentatomidae), one of the most destructive species in soybean cultivation. There is an increasing demand for exploring new microorganisms that have the potential to control this insect. The present study evaluated the susceptibility of E. heros to 15 isolates of different species of the genus Metarhizium. A mortality rate of over 95 % was observed in isolates of M. pingshaense, M. humberi, and M. robertsii in 8 days of experiment. The aerial conidia yield of ESALQ 4395 and ESALQ 3364 isolates stood out with a concentration above 1x109 conidia/g of dry rice, which is similar to commercial isolates. The average lethal concentration of these isolates was 5.1x105 conidia/mL for adult insects, with a 95 % confidence interval of 4.7x105 to 5.4x105 conidia/mL for ESALQ 4395 and 4.8x105 to 5.5x105 conidia/mL for ESALQ 3364. However, no age-dependent mortality was observed since mortality among adults was more pronounced than in immature insects. Although low efficiency of entomopathogenic fungi for controlling stink bugs has been associated with the fungistatic and fungicidal action of the volatile compounds present in the alarm pheromone, the data obtained here demonstrated that this insect is highly susceptible to Metarhizium, especially to species that are not explored commercially in Brazil such as M. humberi, M. pinghaense and M. robertsii.